The Concept of Panutan in Governance Festival Lima Gunung in Magelang Central Java Indonesia - Aswoyo, Joko; Sularso, Sularso (Harmonia: Journal of Arts Research and Education, 2020)
This research is based on fieldwork at a Five Mountain Festival held in Magelang, Central Java, Indonesia. This festival presents performing arts in the regions of Mount Merapi, Merbabu, Andong, Menoreh, and Mount Sumbing. This study intends to explain the concept of panutan in festival governance. Modeling is a significant factor in keeping the Five Mountain Festival alive and sustainable. This study suspects that panutan are one of the guardians of the existence of the Five Mountain Festival. Issues discussed are related to how the panutan concept works, as well as knowing how the implications resulting from the use of the panutan concept in festival governance systems. This study uses qualitative methods with analytical descriptive analysis. Research data were collected through literature studies, documentation studies, interviews, and field observations. The results showed that panutan as organic intellectuals not only created new forms and processes of festival governance but also resulted in the achievement of the advancement of village culture.